2018
DOI: 10.1016/j.jcma.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cancer detection between 18- and 12-core prostate biopsy in Asian patients with prostate-specific antigen levels of 4–20 ng/mL

Abstract: In Asian patients with serum PSA levels between 4.0 and 20.0 ng/mL, 18-core biopsy was associated with superior clinical outcomes to those of 12-core biopsy for detecting prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…A previous study reported that the tumor incidence in a systematic 12core biopsy adding cognitive fusion-targeted biopsy on mpMRI was 88% and 94% in those with PI-RADS V2.0 scores 4 and 5, respectively (21). In our hospital, we do not perform mpMRI targeted biopsy (22). Furthermore, DRE corresponding to MRI is a definitive predictor of PC.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study reported that the tumor incidence in a systematic 12core biopsy adding cognitive fusion-targeted biopsy on mpMRI was 88% and 94% in those with PI-RADS V2.0 scores 4 and 5, respectively (21). In our hospital, we do not perform mpMRI targeted biopsy (22). Furthermore, DRE corresponding to MRI is a definitive predictor of PC.…”
Section: Discussionmentioning
confidence: 81%
“…Bo-Ren Wang et al. ( 31 ) performed 18- and 14-core transperineal biopsy randomly in repeat-biopsy patients and the cancer detection rate was 33.1% vs. 17.6% with an average prostate volume of 48.80 (BD0.37) vs. 45.65 (BD0.31). Ying-Hao Sun et al.…”
Section: Methodsmentioning
confidence: 99%